Strategic Development Planning in the Perspectives of Public Accountability: Lesson from East Java in Indonesia - Puji Handayati; Eddy Sutadji; Bagus Shandy Narmaditya; Dwi Wulandari; Shadi Emad Areef Alhaleh; Putra Hilmi Prayitno (Faculty of Economics, State University of Jakarta., 2021)
This study is intended to identify the level of compatibility documents planning (RPJPD, RPJMD, and RKPD) between provincial and city/regency in East Java of Indonesia. In addition, this study also provides a framework in proposing documents for each city/regency in East Java. This research applied a qualitative method using content analysis. This study employed both primary and secondary data to gain a deeper understanding to the existing phenomenon. The primary data was gathered from in-depth interviews, while secondary data was achieved from several documents owned by each city/regency in East Java provincial. The findings of the study reveal that in general, the substance of the RPJMD in the twenty regencies/cities in East Java of Indonesia is in accordance with the provincial plan. However, there are several different sections of the format in the placement of chapters and sub-chapters of the naming of chapters. In the broader sense, the substance of the RKPD in the twenty regencies/cities is in accordance with the provincial plan.